2003
DOI: 10.1186/1751-0147-44-s1-p107
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Reproductive Function: Association with Energy, Metabolic and Endocrine Status in High Yielding Dairy Cows

Abstract: The effect of energetic, metabolic and endocrine status upon onset of ovarian cyclicity as well as time empty and conception at first service was assessed in 90 multiparous Holstein cows (mean 9'500 kg energy-corrected milk/305 d) in a research farm in Switzerland. Dry matter intake, milk yield and body weight were measured daily from week 2 antepartum (a.p.) through wk 20 postpartum (p.p.). Milk composition was determined 4 times/wk and milk acetone was measured weekly. Blood samples for the determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 0 publications
8
35
2
3
Order By: Relevance
“…A similar tendency towards an increase in cholesterol in the postpartum period was observed in red-and-white multiparous cows after application of extract from human placenta [22]. Previously, it was shown that the blood cholesterol concentration in high-yielding cows in the post-calving period is positively associated with the restoration of sexual circularity and a decrease in open days [27,28]. These data are consistent with the results obtained by us.…”
Section: Introductionsupporting
confidence: 91%
“…A similar tendency towards an increase in cholesterol in the postpartum period was observed in red-and-white multiparous cows after application of extract from human placenta [22]. Previously, it was shown that the blood cholesterol concentration in high-yielding cows in the post-calving period is positively associated with the restoration of sexual circularity and a decrease in open days [27,28]. These data are consistent with the results obtained by us.…”
Section: Introductionsupporting
confidence: 91%
“…A status of NEB decreases LH pulse frequency, growth rate and diameter of the dominant follicle, weight of the corpus luteum (CL), peri-estrous hormone concentrations like estradiol (E2) and progesterone (P4) [11,24,25,[36][37][38][39]. In addition, NEB has been related to more days till the first observed estrus postpartum (pp) [12,16,40], more days till first ovulation [8,11,22,32], more days open pp [41], decreased conception rates following artificial insemination [14,21,25,41] and lower pregnancy rates [15].…”
Section: Negative Energy Balance and Related Disordersmentioning
confidence: 99%
“…Zootec., 44(5): [187][188][189][190][191][192]2015 reserves are at higher risk for metabolic disorders (Bobe et al, 2004), have poorer reproductive performance (Santos et al, 2009), and produce smaller yields of milk (Reist et al, 2003).…”
Section: Introductionmentioning
confidence: 99%